The American Revolution in Georgia, 1763-1789 - Coleman, Kenneth (Georgia Open History Library, 1958)
The American Revolution in Georgia explores the political, economic, and social impacts of the American Revolution throughout the state of Georgia. In this detailed historical study, Kenneth Coleman describes the events leading up to the Revolution, the fighting years of war, and the years of readjustment after independence became a reality for the United States. Coleman investigates how these events impacted Georgia's history forever, from the rise of discontent between 1764 and 1774 to the fighting after the siege in Savannah between 1779 and 1782 and changes in interstate affairs between 1782 to 1789, and more. The American Revolution in Georgia contributes to the complicated history of the American Revolution and its impacts on the South. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.